Politics and ‘spiritual education’ in Simone Weil’s last writings - Fulco, Rita (Logos. Anales del Seminario de Metafísica, 2023)
The aim of this article is to relate the concept of ’force’ to that of ’spiritual education’. Starting from it, we can better understand the link, fundamental for Simone Weil also in the political sphere, between immanence and transcendence. The predominance of force over immanence seems, indeed, to decree the impossibility of a ’just’ politics. Weil shows that awareness of the predominance of force in this world is a first and indispensable step towards justice. This explains the centrality that Weil attaches to the education of attention, particularly for those who are to assume governmental roles. Reflection on politics and justice thus assumes, in the last years of Weil’s life, the role of an ’otherwise than power’, effective on two levels: firstly, as a reflection on power and the forms of government to be given to France liberated from the Nazis; secondly, as a project of true spiritual education for those who will be called to govern at any level.